Microwave-Assisted Extraction of Polysaccharides from Chlorella pyrenoidosa and Its Characterization - Aulia, Margaretha Praba; Azis, Muhammad Mufti; Rochmadi, Rochmadi; Budiman, Arief (Universitas Gadjah Mada, 2025)
This study explored an efficient method for extracting polysaccharides from Chlorella pyrenoidosa using microwave-assisted extraction (MAE) with water as the solvent, a technique consistent with green chemistry principles. The goal was to enhance the yield and quality of polysaccharides for their potential applications as multifunctional active ingredients in the pharmaceutical and functional food industries. Key extraction parameters, including extraction time (10, 20, and 30 min), temperature (80 °C), and solid-to-liquid ratios (1:20, 1:30, 1:40 m/v), were systematically evaluated. The results indicated that a solid-to-liquid ratio of 1:40 m/v at 80 °C for 10 min yielded the highest polysaccharide content (56.64%). FTIR analysis confirmed the presence of pyranose rings in D-glucose and hydroxyl groups, while HPLC identified D-mannose (58.12%) as the predominant sugar, followed by D-glucose (34.46%), D-galactose (3.61%), and L-rhamnose (3.81%). Puriﬁed polysaccharide was composed of major mannose and glucose, a biomolecule very important given that it has wide applications in medical and food industries.